2019
DOI: 10.15244/pjoes/97359
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tillage-Induced Soil Disturbance on Soil Quality

Abstract: Specification of the tillage trends (conventional, reduced, conservation etc.) and endeavours (e.g., energy saving, sustainable) has been made possible in the last 50-60 years. Soil protection has become the main requirement in the soil conservation trend contributing to the implementation of the long-term defence strategy [1]. In the relevant experiments, control often involves conventional tillage as a treatment with negative impact on soil compared with treatments that present a possible solution as direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(41 reference statements)
3
6
0
Order By: Relevance
“…This was attributed to the fact that tillage in the vineyard and olive orchard were carried out more recently than in the cropland (2 years before measurements). It is widely known that tillage reduces, in the short term, topsoil BD [13,32,33]. Natural consolidation and traffic-induced compaction cause the highest soil BD in this study [34].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This was attributed to the fact that tillage in the vineyard and olive orchard were carried out more recently than in the cropland (2 years before measurements). It is widely known that tillage reduces, in the short term, topsoil BD [13,32,33]. Natural consolidation and traffic-induced compaction cause the highest soil BD in this study [34].…”
Section: Discussionmentioning
confidence: 64%
“…Compaction decreases water infiltration, and soil and nutrient losses are high [12]. However, tillage is a millenary tradition that can improve, preserve, or deteriorate soil quality [13]. In the Mediterranean, farmers use tillage to reduce water competition, increase water infiltration, and mix soil amendments [14].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the ratio of different soil fractions such as clods (>10 mm), crumb (2.5-10 mm), fine crumb (0.25-2.5 mm) and dust (<0.25 mm) give the real state about the effect of tillage treatments on soil structure and the consequences of weather effects. The soil structure ratio can be determined from the weight of the fractions [18].…”
Section: Soil Sampling Field Measurements and Laboratory Analysesmentioning
confidence: 99%
“…Residue retention under DC contributed to water conservation through multiple effects on water regime which also has effects on SPR. Very low percentage of stubble residues in P [16,18] may negatively affect soil physical properties in several ways, such as higher soil temperature [52], higher soil evaporation [53], lower soil moisture content (SMC) [54] and greater deterioration of soil structure and soil settling [55] through the kinetic energy of raindrops. However, Afzal et al (2008) [56] found that rapid increase of soil temperature in bare soil, especially in early spring, might be recognized as the crucial factor for faster seed germination.…”
Section: Soil Penetration Resistancementioning
confidence: 99%
See 1 more Smart Citation